Allosteric cross-talk in chromatin can mediate drug-drug synergy - Zenita Adhireksan (Nature Portfolio, 2017)
Allostery and drug-drug synergism can yield potential novel therapies with existing molecules. Here, the authors provide evidence that two unrelated drugs have increased cytotoxicity in cancer cells, which coincides with increased formation of chromatin adducts.